A STUDY ON CONFLICT MANAGEMENT STYLE ADOPTED BY SECONDARY SCHOOL STUDENTS OF DELHI, INDIA IN THE 21STCENTURY - Madhura, Deepti; Muddgal, Alka; Ansari, Mehnaz (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The study aims to find the conflict management style adopted by the senior secondary school students in the private schools of Delhi, India and study the difference in respect to boys and girls. The study further aims to find the relationship between the father’s educational qualification attainment and its influence on the child’s way of handling conflict. During the study certain patterns emerged based on the educational level of attainment of the father.The study was conducted on 716 students and analyses was done on the response provided by them in the questionnaire. It is important to the understand the students of 21st century and their response during conflict. In today’s world the adolescents are in challenging times a lot more than they faced in the past decades. The major reason stated for this in various researchis combination of academic pressures, social media influence, parental expectations, peer relationships. It is also a period for self-discovery and issues on sexuality, identity also enter their life. Thus, it is very important to understand the response they givein the times of conflict with others.